Accumulation of Anthocyanins: An Adaptation Strategy of Mikania micrantha to Low Temperature in Winter - Zhang, Qilei; Zhai, Junjie; Shao, Ling; Lin, Wei; Peng, Changlian (Frontiers in Plant Science, 2019)
The accumulation of anthocyanins in leaves and stems of Mikania micrantha improves its adaptability to low-temperature environments during winter in areas where this species is invasive. The accumulation of anthocyanins in M. micrantha causes the plants to exhibit red coloration when encountering low-temperature environments during winter. Many studies have reported that the accumulation of anthocyanins near the plant surface filters light and improves photoprotection. However, the results of this study showed that the main role of anthocyanins accumulation in M. micrantha during winter was to increase both antioxidant capability and tolerance to low temperature. The results showed that the anthocyanins contents were significantly higher in red leaves and stems than in green leaves and stems, with a more than 60-fold greater content in red leaves than in green leaves. In addition, the total antioxidant capability was significantly greater in red leaves and stems than in green leaves and stems. After 4°C treatment for 12 h, a large amount of reactive oxygen species accumulated in green leaves and stems, and the maximum photochemical efficiency decreased significantly. Compared with that of the green leaves, the net photosynthetic rate of red leaves was significantly higher. The biomass statistics revealed that the dry matter accumulation of M. micrantha plants with relatively large amounts of anthocyanins was significantly greater than that of plants with relatively low anthocyanins levels during the same period. Our results suggest that the accumulation of anthocyanins during winter is an adaptation strategy of M. micrantha to low winter temperatures.